546 INTENSIVE SURVEILLANCE AFTER CURATIVE INTENT SURGERY FOR ESOPHAGEAL CANCER: INITIAL RESULTS OF THE ENSURE STUDY. (17th September 2021) - Elliott, Jessie A; Markar, Sheraz R; Klevebro, Fredrik; Ni, Melody Zhifang; Nilsson, Magnus; Zaninotto, Giovanni; Hanna, George B; Reynolds, John V; ,
Abstract:  : Emerging data demonstrate long-term survival after salvage interventions for local or oligometastatic recurrence after planned curative resection for esophageal cancer, providing rationale for postoperative surveillance. However, the impact of intensive surveillance on oncologic outcome is unknown. This multicenter collaborative study aimed to characterize oncologic surveillance protocols across esophageal cancer centers internationally and determine the independent effect of intensive surveillance on oncologic outcome. Methods: The ENSURE international multicenter study included consecutive patients who underwent surgery with curative intent for cTxNxM0 esophageal cancer from June 2009 to June 2015. Intensive surveillance was defined as use of cross-sectional imaging, at least annually, during the first three postoperative years. The estimated sample size of 4425 provided 90% power to detect a 5% increase in 5-year overall survival (OS, primary outcome measure). Secondary outcome measures included disease-free (DFS) and disease-specific survival (DSS), surveillance strategies, incidence of oligometastatic recurrence, treatment strategies, and HRQOL. The study was registered on ClinicalTrials.gov (NCT03461341). Results: 4597 patients were included. The participating 27 centres undertook mean(SD) 52.3(17.1) esophageal cancer resections annually between 3.5 ± 1.3 attending surgeons. 37%, 11% and 19% centers utilized postoperative surveillance CT, PET-CT and endoscopy, respectively. Among all patients, intensive surveillance was associated with improved OS (HR0.92 [0.85–0.99]) but not DSS (HR0.93 [0.85–1.01]) or DFS (HR0.97 [0.90–1.04]), and on multivariable analysis, intensive surveillance did not provide oncologic benefit (OS HR1.10 [0.99–1.22], DSS HR1.12 [1.00–1.25]), but reduced observed DFS (HR1.19 [1.08–1.31]). Evaluating surveillance modalities, neither surveillance endoscopy nor laboratory tests improved oncologic outcome, however flexible nasolaryngoscopy was associated with improved OS (HR0.84 [0.69–1.0]). Conclusion: ENSURE, the first study powered to assess the impact of postoperative surveillance protocols on oncologic outcome in esophageal cancer, demonstrated no overall survival benefit following intensive imaging surveillance, with reduced observed disease-free survival time. However, routine assessment for secondary aerodigestive malignancies may be of oncologic benefit. The present data do not support the use of intensive imaging surveillance among all patients following esophageal cancer surgery. Further reports detailing subgroup analyses and HRQOL impact are anticipated.